Effect Of Organizational Culture On Organizational Commitment And Nurse Involvement As Intervening Variable: Study at Maternity Hospital Business in Pekanbaru City, Indonesia - Kasmiruddin; Meyzi Heriyanto; Hernimawarti (International Journal of Science, Technology & Management, 2021)
This study aims to prove the indirect effect of organizational culture on organizational commitment through the involvement of nurses in the Maternity Hospital, and whether the effect is greater than the direct effect. This study uses a quantitative approach with explanatory and primary data. Collecting data using a questionnaire with a research sample of 67 nurses. This study uses PLS-SEM with Smart-PLS software in analyzing and processing data. The results showed that organizational culture had a direct effect on organizational commitment, organizational culture had an effect on nurse involvement in hospitals, and nurse involvement had an effect on organizational commitment. However, it was found that organizational culture was not proven to have an effect on commitment through the nurse involvement variable, based on indirect testing. Therefore, the nurse’s involvement variable has not shown its contribution in improving organizational culture and commitment while working at the hospital.